(untitled) (Altre Modernità, 2013)
El Apocalipsis de mi vida (1999) by the Chilean playwright Alexis Moreno, considered an outstanding example in the national dramatic panorama of the late 20th Century, is the result of a punctual ethics and aesthetics research that manages to provide the audience with a deep critical reflection on Chilean reality, the implications with the recent past and the dark future perspectives. The aim of the essay is to focus on the ‘apocalyptic gaze’ offered by the author through the staging of a total failure, treated as a ’way of life’ without any possibility of resolution.